جرجی زیدان وروايته "سلطان صلاح الدين الايوبي ": أدبها و أسلوبها علي نمط الأدباءJurjī Zaydān and his novel, "Sultan Salāhud-Dīn Ayūbī: Its Literature and Style, according to the writers (Al-Qamar, 2021)
The beginning of an imaginary tradition in modern Arabic literature is part of a broader process of restoration and cultural integration. The process involved the creative fusion of two separate forces. One is the rediscovery of the treasures of the Arabic literary heritage and the creation of a "neo-classical" movement. The second is the creation of European fiction in Arabic, their adaptation and imitation, and the final form of the indigenous tradition of modern Arabic fiction. Jurji Zaydan (1861-1914), was an Arabic-Egyptian writer and a well known fictional novelist, journalist, editor and a teacher, and wass far famous Due to its wide serial "Al-Hilal" which contains 23 novels. During Nahda(A cultural movement that flourished in Arabic regions such as: Egypt, Lebanon and Syria in the end of 19th and the start of 20th century.), his motto was to spread the entertainment through Novel to the majority of Arab with their own history. One novel inspired by his thought is "Sultan Salahuddin Ayubi", Within it, there is a fiction like love aspects, as well as distorted history. In order to know the artistic status of this novel, this study will examine it in the style of Arab writers to help new scholars to examine its further works in the same vein.
Keywords: Jurjī Zaydān; Arabic Literature; Novel; Salāhud-Dīn Ayūbī